Cardiac hypertrophy reduction in SHR by specific silencing of myocardial Na/H exchanger - Nolly, Mariela Beatriz (2015)
We examined the effect of specific and local silencing of sodium/hydrogen exchanger isoform 1 (NHE1) with a small hairpin RNA delivered by lentivirus (L-shNHE1) in the cardiac left ventricle (LV) wall of spontaneously hypertensive rats, to reduce cardiac hypertrophy. Thirty days after the lentivirus was injected, NHE1 protein expression was reduced 53.3 ± 3% in the LV of the L-shNHE1 compared with the control group injected with L-shSCR (NHE1 scrambled sequence), without affecting its expression in other organs, such as liver and lung. Hypertrophic parameters as LV weight-to-body weight and LV weight-to-tibia length ratio were significantly reduced in animals injected with L-shNHE1 (2.32 ± 0.5 and 19.30 ± 0.42 mg/mm, respectively) compared with L-shSCR-injected rats (2.68 ± 0.06 and 21.53 ± 0.64 mg/mm, respectively). Histochemical analysis demonstrated a reduction of cardiomyocytes cross-sectional area in animals treated with L-shNHE1 compared with L-shSCR (309,81 ± 20,86 vs. 424,52 ± 21 μm2, P < 0.05). Echocardiography at the beginning and at the end of the treatment showed that shNHE1 expression for 30 days induced 9% reduction of LV mass. Also, animals treated with L-shNHE1 exhibited a reduced LV wall thickness without changing LV diastolic dimension and arterial pressure, indicating an increased parietal stress. In addition, midwall shortening was not modified, despite the increased wall tension, suggesting an improvement of cardiac function. Chronic shNHE1 expression in the heart emerges as a possible methodology to reduce pathological cardiac hypertrophy, avoiding potentially undesired effects caused from a body-wide inhibition of NHE1.